Tailoring Inorganic Halide Perovskite Photocatalysts toward Carbon Dioxide Reduction. Issue 6 (16th March 2022) - Zhang, Xingmo; Tang, Rui; Li, Feng; Zheng, Rongkun; Huang, Jun
Abstract : In recent years, photocatalytic carbon dioxide reduction has emerged as an attractive strategy to settle the global warming and energy crisis by converting CO2 into valuable chemicals utilizing solar energy. All‐inorganic halide perovskites (PVKs), as a class of promising light‐harvesting materials with outstanding optoelectronic properties and considerable stabilities, have received dramatic attention in the field of photocatalytic CO2 reduction reaction (CO2 RR). In this review, the recent progress of PVK catalysts for CO2 RR is systematically summarized and evaluated according to the modification strategies and their mechanisms. The working principles of CO2 RR are first introduced. The main strategies for improving the photoelectrochemical performance are then discussed and their recent developments are summarized. Finally, the current challenges, including instability, charge recombination, and insufficient active sites, and future research opportunities for further development are addressed. Abstract : This review provides a comprehensive overview of the recent progress on photocatalytic CO2 reduction reaction based on perovskite (PVK)‐related catalysts from the structure–component engineering perspective to clarify its influence on carrier transfer, stability, and product selectivity of PVK‐based photocatalysts. Meanwhile, the current challenges and future potential research directions of PVK‐based photocatalysts are also pointed out.